Pengaruh Keberadaan Ruang Terbuka Hijau terhadap Tingkat Karbon Dioksida (Co2) Perkotaan di Kota Jayapura : (Studi Perbandingan Antara Ruas Jalan Percetakan Dan Kawasan Dok V Atas) - Carlos Petter Timotius; Elisabeth V. Wambrauw; Juliani Wairata (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Green Open Space (GOS) is an essential element in urban spatial planning that functions to maintain air quality and ecosystem balance. This research aims to analyze the influence of GOS on the concentration levels of Carbon Dioxide (CO2​) in the urban area of Jayapura City. The study locations were focused on two areas with distinct characteristics: Jalan Sam Ratulangi, which has high vegetation coverage, and Jalan Percetakan, which is dominated by built-up areas and dense commercial activity. The methods used include spatial analysis utilizing Landsat 8 satellite imagery Band 4 (Red) and Band 5 (NIR) to calculate the NDVI (Normalized Difference Vegetation Index), a vegetation time series analysis from 2019–2024, and direct CO2​ concentration measurements taken at three different times (morning, noon, afternoon). The data was processed using ArcGIS with the Kriging Interpolation method to generate spatial distribution maps of CO2​ in both locations. The results show that Jalan Sam Ratulangi has a GOS area of 6.13 ha (94%), while Jalan Percetakan has only 2.95 ha (31%). This difference significantly impacts CO2​ levels, with an average concentration of 484 ppm at Sam Ratulangi, which is lower than Percetakan's average of 567 ppm. The highest CO2​​ value at Percetakan reached 649 ppm during the afternoon, whereas Sam Ratulangi recorded only 488 ppm. This study proves that the wider and healthier the GOS, the lower the CO2​​ concentration detected. These results demonstrate that vegetation plays a significant role in reducing carbon emissions in urban areas, supporting the crucial role of GOS in maintaining air quality and supporting sustainable urban development in Jayapura City.